THE INFLUENCE OF INTENAL AUDIT ON FINANCIAL MANAGEMENT IN MARSABIT COUNTY GOVERNMENT- KENYA - Dambala, Abudo Yohana; Rintari, Dr. Nancy; Mutea , Fredrick (International Journal of Finance, 2021)
Purpose: The purpose of this study was to determine the effect of internal audit on the financial management in the County Government of Marsabit. Methodology: The study adopted descriptive survey was adopted for this study. The targeted study population was 63 staff members who are Job group K and above from the department of Finance in the directorate of Accounts, Revenue, Procurement and Internal Audit. The study employed simple structured questionnaires to gather primary data which was analyzed using SPSS. Results: The study revealed that internal audit function had a significant influence on financial management at the county government of Marsabit (r=0.691, p=0.00) Unique contribution to theory, policy and practice: Good financial management is very essential in protecting the public funds. This study encourages good practices of accountability, transparency and wealth creation with public funds. The study is beneficial to not only Marsabit County but other counties in Kenya. The study concludes that the Marsabit County has a functional internal audit committee and internal auditors perform their duties with great autonomy and independence. The study further concludes that internal audit has strong positive effect on the financial management in Marsabit County. The study recommends internal audit to be well staffed and resourced so that it is able to carry out regular audits of the county government. This will improve financial management of the County Government since it has been established that internal audit has strong positive effect on the financial management. Additional research can be conducted in the National government on factors influencing financial management and drawing comparisons.